PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN CENTRO RECREACIONAL DE BOLOS (BOWLING), EN LA CIUDAD DE LOJA - Aguinsaca Guachanamá, Luz Angélica (2016)
The city of Loja, currently manages the entertainment industry and people known for their services, as currently does not have a recreational bowling center, allowing them to recover those games that were present in infancy and have fun in a healthy way, because in this industry, are also embedded bars and clubs, services, not being used consciously, they can lead to social risk. To resolve this problem, this project the following objectives: Conduct a market study to identify the demand and supply of the services of a recreational bowling center; Make a marketing plan to determine how service delivery, pricing, distribution channels and how to promote the services of a recreational bowling center; Conduct a technical study to determine the size, location and service engineering recreational bowling center; Designing the organizational and legal structure for recreational bowling center; Develop a financial study to establish the amount of investment and financing, cost analysis, establishment of revenue and the statement of income or expense of the project, finally; Perform financial evaluation of the company, making use of all indicators such as NPV, IRR, cost benefit analysis, sensitivity analysis, and capital recovery period for determining the profitability of the project. To fulfill the objectives, methodology, same that allows outline the steps or processes to follow this methodology refer to the methods and techniques were employed, such as follows: deductive and inductive method, with which It determined in general and specifically the needs of users with respect to the service. 8 The survey technique was applied during the market survey on the sample size. According to the methodology used to obtain the sample size, we proceeded to segment the population, which consisted of the same people aged 18 to 40 years of both sexes. Therefore urban population of Loja is a total of 170.280 inhabitants according to the 2010 census, the segment with which the project is 56.124 people worked. Once the segment obtained inhabitants proceeded to project until 2015, which resulted in 63.965 inhabitants. Followed formula was applied to determine the sample size obtaining a result of 382 respondents. With the methodology used, it was to obtain the following results: the demand the number of potential plaintiffs, who are practicing some kind of sport was determined according to the results of the surveys is 79% in absolute terms whose amount is 50.532 potential applicants for 2015 of 63.965 people, the number of applicants per year are increasing, this is people per year, the growth rate increased by 2.65% this year above, as it explained in the methodology, ending with an amount of 57 593 potential claimants, for a total of 72.902 people by 2020. Of the total of potential applicants, the amount of actual plaintiff, who are those who are currently using the service whose relative value is 47% of this value in absolute is 23.750 amounts is real claimants 50,532 potential claimants for 2015 was determined , ending in 2020 with 27,069 real potential claimants. After determining the number of actual applicants the sum of effective applicants, who are the people who will use the new service to be offered is set, 9 this being a value of 100% of actual claimants, ie 2015 effective plaintiffs they are 23,750 and 2020 will be 27,069 troop’s plaintiffs. These amounts will be continued with the screening of demand, taking the average use per capita as determined in the analysis of the surveys, whose value is 12 hours a year who use the service person, this value by multiplying with effective demand projected in an amount of 292,555 hours of service for the year 1 (2016) demand was obtained, and ends with an amount of 324,822 hours of service for year 5 (2020). Once completed the study of the plaintiffs, they proceeded to carry out the study of the bidders, the same as not having a dedicated company to offer this service, could not be carried out. Therefore the amount of supply of service is zero within the city of Loja. After determining the projected demand proceeded to obtain the balance between supply and demand to determine the existence of unmet same as the absence of supply is the same demand projected whose value for the zero year is 285,002 hours, followed by 633,869 hours for year 1, and ends with a total of 703,781 hours by 2020. On the technical study, the capabilities of both installed and used is determined, with a total capacity utilization of 45.072 annual services. With this capability the market share, it is 7.11% for year one and 6.40% for the fifth year was determined. He completed the technical study, proceeded to execute the financial study, where costs are detailed to acquire: fixed assets, deferred assets and cover 10 with operating costs, where intervenes production costs and administrative expenses and those of sales. Having identified these items on a monthly basis for investment and annually to the proformado budget, we continued to establish the unit price of the service itself that for year one is $ 1.84 followed the year two with a monetary value of $ 1.90 it is for the five year cost of service of $ 2.09. It followed the cost of service, continued with the determination of cash flows, which served me served to develop the financial evaluation, in which the following results were obtained: Net Present Value $ 7.968,86; Internal rate of return 18.37%; Benefit Cost Ratio 0.54 cents of profit for every dollar invested; Capital Recovery Period 3 years 6 months and 5 days; in the Sensitivity analysis The project it´s in the capacity to the increase of costs in 8,5% and decrease of revenues in 5.5%.